2019
DOI: 10.1093/jas/skz053.016
|View full text |Cite
|
Sign up to set email alerts
|

139 Evaluation of cool-season annuals or reduced labor supplementation systems for wintering cowcalf pairs

Abstract: Cattle producers typically feed hay and supplement for a 90- to 120-d window to maintain cows during the winter in Alabama. Relying on stored feeds can increase management system costs and labor needs. The objective of this demonstration project was to compare alternative, reduced labor management systems commonly used by producers in the region for diet quality and animal performance responses. A 75-day trial evaluated the use of three systems (n = 3 replications per system): 1) rotationally grazed-winter ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The presence of clover in the mixture increases the CP concentration [ 11 ], which was evident in the current study since WB had the lowest range. In a grazing study using the ROC mixture; Mason et al [ 22 ] observed a 21.5% CP for the mixture. While Marchant et al [ 23 ] reported a 19.5% CP for the wheat + annual ryegrass mixture under continuous stocking.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of clover in the mixture increases the CP concentration [ 11 ], which was evident in the current study since WB had the lowest range. In a grazing study using the ROC mixture; Mason et al [ 22 ] observed a 21.5% CP for the mixture. While Marchant et al [ 23 ] reported a 19.5% CP for the wheat + annual ryegrass mixture under continuous stocking.…”
Section: Discussionmentioning
confidence: 99%